DESKRIPSI PENGELOLAAN PERSEDIAAN OBAT DI RUMAH SAKIT PMI BOGOR - SUSILAWATI GUNAWAN; Cie Vien Aravis; Firmansyah Firmansyah (Jurnal Mitra Kesehatan, 2023)
Inappropriate drug management will open up opportunities for an oversupply ogf drugs and vancancies in the drug supply. Vancancies can affect the quality and cost of hospital services. Ineffectiveness and inefficiency in drug management will hurt medical, social, and economic aspects. Hospital, by not being able to reach the point of success, reduce the quality of service and patient satisfaction. The research objective was find out the description of drug logistic management at the PMI Bogor Hospital pharmacy installation from December 2022- January 2023. This type of research wa case study. Data collection tehniques include in-depth interviews, observation, and literature studies. There were six research informants. Data processing was carried out by reducing data, categorizing it into each sub-problem through short narratives, directing and removing inappropriate data and organizing the data so the conclusions can be drawn and verified. Data analysis uses the methods of generating rich data, famailiarizing oneself with data, mapping, and interpretation. The result of the research on drug logistics management process are quite good, but there are several problems found, namely that evaluation and monitoring of durg supplies rerely carried out, traning for human resources for pharmaceutical warehouses has never been carried out, additional human resources are needed for pharmateutical warehouses is expected to incr3ease so that there is no accumulations of goods outside the warehouse, and incidents of running out of pharmateutical supplies and not being able to order pharmaceutical supplies because they are have not paid for the previous order.